Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.omtn.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Imbalance Contributes to COPD Deterioration by Enhancing IL-17a Production via miR-122 and miR-30a

Abstract: The changes of microbiota in lungs could change interleukin-17a (IL-17a) expression by altering microRNAs (miRNAs) profile, thus contributing to the pathogenesis of chronic obstructive pulmonary disease (COPD). In this study, we aimed to study molecular mechanisms’ underlying effect of microbiota imbalance on COPD deterioration. Real-time polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) were performed to analyze expression of miRNAs and IL-17a mRNA. ELISA was used to evaluate abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
6
7
0
Order By: Relevance
“…Importantly, we further observed a 5-fold decrease in the expression of miR-122-5p on comparing miRNA population from lung-derived exosomes from COPD patients versus healthy smokers. Our results are in accordance with previous literature (50-52). For instance, Zhu et al (2020) demonstrated the downregulation of miR-122-5p in the sputum and plasma of COPD patients and proved that it functions as a negative regulator of IL-17A production (50).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Importantly, we further observed a 5-fold decrease in the expression of miR-122-5p on comparing miRNA population from lung-derived exosomes from COPD patients versus healthy smokers. Our results are in accordance with previous literature (50-52). For instance, Zhu et al (2020) demonstrated the downregulation of miR-122-5p in the sputum and plasma of COPD patients and proved that it functions as a negative regulator of IL-17A production (50).…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with previous literature (50-52). For instance, Zhu et al (2020) demonstrated the downregulation of miR-122-5p in the sputum and plasma of COPD patients and proved that it functions as a negative regulator of IL-17A production (50). It is pertinent to mention here that though we did not find any commonly altered miRNAs in the exosomes from BALF or lung tissues of COPD patients, we found links that associate miRNA-mediated modulation of IL17-signalling amongst the diseased individual.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with previous literature (50)(51)(52). For instance, Zhu et al (2020) demonstrated the downregulation of miR-122-5p in the sputum and plasma of COPD patients and proved that it functions as a negative regulator of IL-17A production (50). It is pertinent to mention here that though we did not find any commonly altered miRNAs in the exosomes from BALF or lung tissues of COPD patients, we found links that associate miRNA-mediated modulation of IL17-signalling amongst the diseased individual.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with previous literature (50)(51)(52). For instance, Zhu et al (2020) demonstrated the downregulation of miR-122-5p in the sputum and plasma of COPD patients and proved that it functions as a negative regulator of IL-17A production (50).…”
Section: Discussionsupporting
confidence: 93%
“…In the next step, hPASMCs and rPASMCs were co-transfected with the wild-type or mutant-type MALAT1 promoter in conjunction with miR-146a mimics or a negative control miRNA. At 24 h after the transfection was started, the luciferase activity in transfected cells was evaluated by using a dual luciferase reporter gene assay kit (Promega) on a TD-20/20 luminometer (Turner Biosystems, Sunnyvale, CA, United States) based on the general protocols provided by the manufacturers of both the reporter gene assay kit and the luminometer ( Zhou et al, 2020 ; Zhu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%